From the Cradle to the Grave: Age Differences in Attachment From Early Adulthood to Old Age. Issue 2 (5th February 2013) - Chopik, William J.; Edelstein, Robin S.; Fraley, R. Chris
Abstract Objective Although attachment dynamics are thought to be important across the life span, relatively few studies have examined attachment processes beyond young adulthood. Extant research on age differences in attachment orientation has yielded conflicting results and interpretations. The purpose of this study was to provide a more complete picture of age‐related differences in attachment anxiety and avoidance. Method We examined attachment anxiety and avoidance in 86, 555 Internet respondents (71.8% female) ranging in age from 18 to 70. Results We found that attachment anxiety was highest among younger adults and lowest among middle‐aged and older adults. Attachment avoidance showed less dramatic age differences overall but was highest among middle‐aged adults and lowest among younger and older adults. In addition, partnered individuals reported lower levels of attachment anxiety and avoidance compared to single individuals, particularly in younger and older adulthood. Women also reported slightly higher anxiety and avoidance compared to men, especially in young adulthood. Conclusions Findings are discussed in the context of life span changes in social roles, normative personality development, and emotion regulation throughout adulthood.